2006
DOI: 10.1103/physrevc.74.064301
|View full text |Cite
|
Sign up to set email alerts
|

Screening effects in superfluid nuclear and neutron matter within Brueckner theory

Abstract: Effects of medium polarization are studied for 1 S0 pairing in neutron and nuclear matter. The screening potential is calculated in the RPA limit, suitably renormalized to cure the low density mechanical instability of nuclear matter. The selfenergy corrections are consistently included resulting in a strong depletion of the Fermi surface. All medium effects are calculated based on the Brueckner theory. The 1 S0 gap is determined from the generalized gap equation. The selfenergy corrections always lead to a qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
280
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(309 citation statements)
references
References 36 publications
24
280
5
Order By: Relevance
“…Recently, ab initio quantum Monte Carlo calculations have been carried out for low-density infinite neutron matter (k F,n 0.5 fm −1 ) [48], with an effort to understand the differences with other Monte Carlo results [49][50][51]. A quenching of the mean-field pairing gap is predicted, resulting in a larger pairing gap than what previous calculations found [52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 94%
“…Recently, ab initio quantum Monte Carlo calculations have been carried out for low-density infinite neutron matter (k F,n 0.5 fm −1 ) [48], with an effort to understand the differences with other Monte Carlo results [49][50][51]. A quenching of the mean-field pairing gap is predicted, resulting in a larger pairing gap than what previous calculations found [52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 94%
“…Such kind of calculations are still not available for WS cells, mainly because of the computational time requested. According to our findings, a possible alternative could be represented by performing calculations in the infinite systems of both collective excitations [45][46][47] and pairing gaps [48]. Such results could be then used to fit an effective zero range pairing interactions.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known, however, that many-body effects can significantly modify the HFB results. Several studies have found that the pairing gap in neutron matter is quenched by spin fluctuations [11][12][13][14], but results obtained in uniform matter cannot be directly extrapolated to the actual case of the inhomogeneous inner crust. In fact, many-body effects in (isolated) atomic nuclei are strongly dominated by the coupling between single-particle and collective surfacelike degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%